Risk factors for the progression from acute recurrent to chronic pancreatitis among children in China - Jingqing Zeng; Jiayu Zhang; Yabin Hu; Xiumin Wang; Zhaohui Deng (Frontiers Media S.A., 2022)
BackgroundRisk factors for progression from acute recurrent pancreatitis (ARP) to chronic pancreatitis (CP) in children are poorly understood.AimTo summarize the clinical characteristics of children with ARP and CP, identify the risk factors of CP, and investigate the factors associated with rapid progression from initial onset of ARP to CP.MethodsThe following variables were included in the risk factor analysis: sex, age at onset, family history, pancreas or biliary tract structural abnormalities, and genetic variations. Univariate and multivariate logistic regression analyses were used to assess the risk factors of CP. The Kaplan-Meier curves of the ARP progression to CP for various risk factor groupings were constructed and compared using the log-rank test. The Cox proportional hazard regression model was fitted to estimate the hazard ratio (HR) of progression to CP for each risk variable.ResultsIn total, 276 children were studied, of whom 136 progressed to CP. Among them, 41 had pancreatic duct obstructive disease; 105 underwent genetic testing, of whom 68 were found to have genetic variations. Among the remaining 140 patients who did not progress to CP, 61 had biliary obstructions. Forty-three of these children underwent genetic testing, and 15 were found to have genetic variations. Risk factor analysis showed that children with gene mutations were at a higher risk of progressing to CP [odds ratio (OR) = 3.482; 95% confidence interval (CI): 1.444-8.398; P = 0.005]; children with pancreas divisum (PD) had a higher risk of CP than those without (OR = 8.665; 95% CI: 1.884, 9.851; P = 0.006). Further, children whose first ARP occurred at an older age might develop CP faster (HR = 1.070; 95% CI: 1.003, 1.141; P = 0.039). Children with gene mutations had a faster rate of progression to CP after onset than children without gene mutations (HR = 1.607; 95% CI: 1.024, 2.522; P = 0.039), PRSS1 gene mutations were more associated (P = 0.025). There was no difference in the rate of progression from ARP to CP in children with PD (P = 0.887); however, endoscopic retrograde cholangiopancreatography (ERCP) intervention delayed the progression to CP in ARP patients with PD (P = 0.033).ConclusionPRSS1 gene mutations and PD are key risk factors for ARP progression to CP in children. PD itself does not affect the disease progression rate, but therapeutic ERCP can be beneficial to patients with ARP with symptomatic PD and delay the progression to CP.